PERAN KELUARGA DAN MASYARAKAT DALAM MENDUKUNG SERTA MEMENUHI HAK DISABILITAS DI KELURAHAN PONDOK JAGUNG TANGERANG SELATAN - Ramadhan, Alfien; Nordiantika, Fina Tryas; Panjaitan, Frengky Franciskus; Widjaja, Mohammad Taufiq Iskandar; Solihat, Siti (Praxis: Jurnal Pengabdian Kepada Masyarakat, 2024)
People with disabilities tend to feel inferior when interacting in society, both in their living environment and in their educational environment. Therefore, people with disabilities need the role of family and community in increasing self-confidence so that they have confidence in their own abilities so that they can carry out all activities according to their interests, are able to be responsible, and have the courage to interact with other people, and can explore their own potential. The focus of research in this journal is: 1) What are the forms of social support for people with disabilities? 2) What are the rights of people with disabilities? 3) What problems do people with disabilities have? 4) How do you support children with disabilities in the family? 5) What is the role of society in the education of children with disabilities? The aim of this research is to find out: 1) Social support for people with disabilities. 2) Rights for people with disabilities. 3) Problems of people with disabilities. 4) Supporting children with disabilities since they are in the family. 5) The role of society in the education of children with disabilities. A qualitative approach using literature studies is the main method for conceptually describing studies of support and fulfillment of rights from families and communities for people with disabilities. This research comes to the conclusion that: 1) The role of families in Pondok Jagung Subdistrict, South Tangerang in supporting and fulfilling the rights of people with disabilities is to implement the education patterns that people with disabilities need and fully support their development. 2) The role of the community in Pondok Jagung Subdistrict, South Tangerang in supporting and fulfilling the rights of people with disabilities, namely first, teachers apply learning models according to the needs of people with disabilities, providing opportunities and responsibilities to develop their potential. Second, society provides opportunities for people with disabilities to interact with the surrounding environment. 3) The role of the community in Pondok Jagung Subdistrict, South Tangerang in supporting families of people with disabilities is by providing support, both morally and socially